2020
DOI: 10.1088/2053-1591/ab636d
|View full text |Cite
|
Sign up to set email alerts
|

Study of transport, magnetic and magnetocaloric properties in Sr2+ substituted praseodymium manganite

Abstract: The magnetotransport, magnetic and magnetocaloric properties in the polycrystalline Pr 1−x Sr x MnO 3 (0.20x0.40) have been studied. The X-ray diffraction peaks for the composition x=0.20, 0.33 and 0.40 have been indexed with orthorhombic structure having Pnma space group, whereas x=0.25 composition has been indexed to R-3c space group having rhombohedral symmetry. The substitution of Sr 2+ at Pr 3+ site shows an increase in metal-insulator transition temperature (T MI ) and ferromagnetic ordering temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…An investigation of electrical behavior for polycrystalline samples x = 0.02; 0.05; 0.1 and 0.2 was performed using the four-point probe method in external fields of µ 0 H = 0 T; 1 T; 2 T in temperature range of 10-290 K. For the sample with x = 0.3 fields of up to 5 T were used. Data were used to estimate metal-insulator transition temperature T p and magnetoresistivity MR according to the following equation [23]:…”
Section: Electrical Measurementsmentioning
confidence: 99%
“…An investigation of electrical behavior for polycrystalline samples x = 0.02; 0.05; 0.1 and 0.2 was performed using the four-point probe method in external fields of µ 0 H = 0 T; 1 T; 2 T in temperature range of 10-290 K. For the sample with x = 0.3 fields of up to 5 T were used. Data were used to estimate metal-insulator transition temperature T p and magnetoresistivity MR according to the following equation [23]:…”
Section: Electrical Measurementsmentioning
confidence: 99%
“…The obtained experimental values are summarized in Table 2. Moreover, the theoretical effective magnetic moment of Pr 1−x Sr x MnO 3 can be obtained using the following relation [79],…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…From a practical point of view, the Pr 1−x Sr x MnO 3 series are one of the most interesting perovskites for magnetic refrigeration due to their large magnetization near to the ambient temperature and their strong chemical resistance that compensates for their relatively moderate magnetocaloric effect [76,77]. Additionally, the substitution approach can be used to modify the Curie temperature, with a change of about 4 K in T c per percent (%) of Sr [78,79]. In the performed study by Repaka et al [80], the magnetization and the magnetocaloric effect of the polycrystalline Pr 0.6 Sr 0.4 MnO 3 were particularly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Manganese-based perovskite system (called manganites with the general formula as R 1-x A x MnO 3 , where R = La, PrK and A = Ca, Sr, BaK) is one of the magnetocaloric materials of wide interest because they have some advantages (such as simple fabrication, stability under normal conditions, quite large electrical resistivity, and low costK) and exhibit interesting electrical and magnetic properties as well as rich phase diagram [1][2][3][4]. Partial substitution of the R/A position created a mixed valence of Mn ions (Mn 3+ and Mn 4+ ), which causes the appearance of double exchange interactions exhibiting ferromagnetic (FM) between the Mn 3+ -Mn 4+ pairs.…”
Section: Introductionmentioning
confidence: 99%
“…These interactions coexist and compete with antiferromagnetic super exchange interactions caused by covalent Mn ion pairs (Mn 3+ -Mn 3+ and Mn 4+ -Mn 4+ ). Previous studies have shown that the electromagnetic effects in manganites often occur around the electrical (metal-insulator) and magnetic (ferromagnetic-paramagnetic (FM-PM)) phase transitions [2,[5][6][7][8], and they are strongly influenced by the average ionic radius at the R/A-site and the ratio of Mn +3 /Mn 4+ [2-5, 7, 8]. Among them, the Pr 1-x Sr x MnO 3 system is considered as one of the most interested ones.…”
Section: Introductionmentioning
confidence: 99%